The Effect of Phenazine-1-Carboxylic Acid on Mycelial Growth of Botrytis cinerea Produced by Pseudomonas aeruginosa LV Strain - Simionato, Ane S.; Navarro, Miguel O. P.; de Jesus, Maria L. A.; Barazetti, André R.; da Silva, Caroline S.; Simões, Glenda C.; Balbi-Peña, Maria I.; de Mello, João C. P.; Panagio, Luciano A.; de Almeida, Ricardo S. C.; Andrade, Galdino; de Oliveira, Admilton G. (Frontiers in Microbiology, 2017)
One of the most important postharvest plant pathogens that affect strawberries, grapes and tomatoes is Botrytis cinerea, known as gray mold. The fungus remains in latent form until spore germination conditions are good, making infection control difficult, causing great losses in the whole production chain. This study aimed to purify and identify phenazine-1-carboxylic acid (PCA) produced by the Pseudomonas aeruginosa LV strain and to determine its antifungal activity against B. cinerea. The compounds produced were extracted with dichloromethane and passed through a chromatographic process. The purity level of PCA was determined by reversed-phase high-performance liquid chromatography semi-preparative. The structure of PCA was confirmed by nuclear magnetic resonance and electrospray ionization mass spectrometry. Antifungal activity was determined by the dry paper disc and minimum inhibitory concentration (MIC) methods and identified by scanning electron microscopy and confocal microscopy. The results showed that PCA inhibited mycelial growth, where MIC was 25 µg mL-1. Microscopic analysis revealed a reduction in exopolysaccharide (EPS) formation, showing distorted and damaged hyphae of B. cinerea. The results suggested that PCA has a high potential in the control of B. cinerea and inhibition of EPS (important virulence factor). This natural compound is a potential alternative to postharvest control of gray mold disease.